WOMANS RECONCILIATION OF DOMESTIC LIFE AND SELF DEVELOPMENT IN ELIZABETH STUART PHELPSS THE ANGEL OVER THE RIGHT SHOULDER - Juliasih K. (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2012)
Women face an everlasting issue of dividing their time for domestic life and self-development as the work of Elizabeth Stuart Phelps, The Angel Over the Right Shoulder, portrays. It shows that there is inequality between man and woman. The research aims to investigate the main reasons of the problem. It shows that men and women have their own language. This research applies Ecriture Feminine which bases itself on the belief that feminity is qualitatively different from masculinity andit needs an alternative form of language in order to express adequately the difference, something which would benefit both men and womenKeywords : system, unity, reconciliation, Feminine Ecriture